English language skills and becoming a global entrepreneur: lessons for entrepreneurship education - Sheikh Ahmad, Ismail; Yusof Khan, Zarinah Jan (Society for Research and Knowledge Management, 2023)
This paper discusses the results of a case study that focused on the importance of English language skills in helping students become global entrepreneurs. A critical element that is often missing in courses on Entrepreneurship Education is the inclusion of the language component that helps build oral English proficiency. In the entrepreneurship education courses, the importance of teaching English skills to prepare students to become global entrepreneurs is seldom instilled among students—an especially crucial aspect when teaching students for whom English is a second or foreign language—as it would not only motivate them to use English more, but also help them overcome their challenges in using English. By using an online survey and focus group discussions, this study obtained the views of 177 undergraduate students of an Entrepreneurship Education course conducted by the Faculty of Economics of a Malaysian public university. The attitudes of the students towards using English for entrepreneurship and the challenges they faced in doing so are highlighted, and implications are drawn for teaching English in entrepreneurship courses.